Answer:
x = 1
y = -1
z = 2
Explanation:
You have the following system of equations:
![x+2y-z=-3\ \ \ \ \ (1)\\\\2x-y+z=5\ \ \ \ \ \ (2)\\\\x-y+z=4\ \ \ \ \ (3)](https://img.qammunity.org/2021/formulas/mathematics/high-school/o610g1nyf74f70bnhvh86w5o5md85kacbp.png)
First, you can subtract euqation (3) to equation (1):
x + 2y - z = -3
-x +y -z = - 4
0 3y -2z = -7 (4)
Next, you can multiply equation (3) by 2 and subtract it to equation (2):
2[ x -y + z = 4]
-2x +y -z = -5
0 -y + z= 3 (5)
You multiply equation (5) by 2 and sum (5) with (4):
2[ -y + z = 3]
3y -2z= -7
y + 0 = -1
Then y = -1
Next, you replace y=-1 in (5) to obtain z:
-(-1) + z = 3
z = 2
Finally, you can replace z and y in the equation (3) to obtain x:
x - (-1) + (2) = 4
x = 1